Residual Infantile Feeding History and Speech Outcomes in Preschool-Age Children: A Balkan Cross-Sectional Study on Parent-Led Weaning Implications - Poposka, Ana; Kacka, Muljaim (International Journal of Child Health and Nutrition, 2025)
This study examines the relationship between residual infantile feeding history and subsequent speech sound disorders (SSD) in preschool-aged children within the Balkan region. It specifically investigates how traditional parent-led weaning practices influence the type and placement of SSD manifestations through their impact on early oromotor development. A cross-sectional analysis was conducted with 72 children, aged 3 to 6 years, diagnosed with moderate to severe SSD across two clinical centers in Kosovo and North Macedonia. Standardized articulation assessments and caregiver-completed developmental questionnaires were utilized to evaluate speech outcomes and feeding patterns. Key findings revealed significant associations: prolonged non-nutritive sucking (NNS) was strongly linked to anterior speech sound disorders and distortion errors; delayed progression to textured foods was correlated with middle/palatal SSD patterns; and oral sensory dysfunction was notably associated with substitution errors. The study underscores the clinical importance of early feeding interventions and individualized therapy approaches. Targeted strategies such as lingual strengthening for omissions and sensory-motor techniques for substitutions are recommended. These findings contribute to clinical practice and highlight the need for increased awareness and prevention of non-normative feeding patterns in the Balkan pediatric population.